Pengaruh Pakan Limbah Jeroan Ikan Nila dan Limbah Tomat Terhadap Pertumbuhan serta Kadar Protein Maggot BSF (Hermetia illucens) - Auriel Zahra Alisha; Euis Nursaadah; Nirwana Nirwana; Ariefa Primair Yani; Lukmanul Hakim; Sutarno Sutarno (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to analyze the effect of tilapia offal waste and tomato waste on the growth and protein levels of BSF maggots. This research analyzes the ratio of mass, length and thickness as well as the protein content of maggots on the influence of the feed used. This research used a Completely Randomized Design (CRD) consisting of 5 treatments with 3 repetitions. The results showed that the P1 100% fish treatment was the best variation for mass, namely 0.27. Treatment P1 100% fish is the best variation for length, namely 22.40. Treatment P1 100% fish and P2 75% fish and 25% tomatoes is the best variation for thickness, namely 5.85, and Treatment P4 25% fish and 75% tomatoes is the best variation for protein content, namely 22.01%. In conclusion, feeding fish waste and tomato waste on growth and protein content in BSF maggots affects mass, length, thickness and protein content. Keywords: Protein Content, Fish Offal Waste, Maggot, Tomato